2010
DOI: 10.1007/s10147-010-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of PET-FDG in primary breast cancer based on histopathological and immunohistochemical prognostic factors

Abstract: SUV, a preoperative and noninvasive metabolic parameter, correlates with other known prognostic factors in breast cancer. This study provides valuable insight into the usefulness of FDG-PET/CT for preoperative staging of patients with triple-negative and poorly differentiated breast tumors but not for evaluating axillary lymph nodes and lobular carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 24 publications
7
43
0
2
Order By: Relevance
“…Some studies have demonstrated a relationship between SUV and hormone receptors such as ER [16,21] and PR [21]. We found lower SUVmax1 and SUVmax2 in ER-and PR-positive patients.…”
Section: Suvmax Of the Primary Lesionsupporting
confidence: 45%
See 2 more Smart Citations
“…Some studies have demonstrated a relationship between SUV and hormone receptors such as ER [16,21] and PR [21]. We found lower SUVmax1 and SUVmax2 in ER-and PR-positive patients.…”
Section: Suvmax Of the Primary Lesionsupporting
confidence: 45%
“…In a study performed by Heudel et al [21], the low SUVmax level in T1 tumors was thought to be related to a partial volume effect. Our study did not include T1a-T1b tumor sizes to avoid partial volume effects in our results.…”
Section: Suvmax Of the Primary Lesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results have been reported as the correlation between FDG uptake and PR status. Some studies have claimed higher SUVmax in the PR (−) breast cancer [39,40], but other reports showed no association between PR status and FDG uptake [41,42]. Ekmekcioglu et al [42] suggested that the cut-off level of the PR limit of positivity might be relevant to the result.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have demonstrated good correlations between primary tumor FDG uptake on PET/CT, expressed as the maximum standardized uptake value (SUV max ), and clinicopathological findings that are known to be important prognostic indicators in breast cancer patients [10][11][12][13][14][15][16][17]. A higher SUV max is reported to be significantly associated with estrogen receptor (ER) negativity, progesterone receptor (PR) negativity, human epidermal growth factor receptor 2 (HER2) positivity, a high Ki-67 index, a bigger tumor size, a higher histological grade, presence of axillary lymph node (LN) metastasis, and a higher stage.…”
Section: Factors Correlated With Fdg Uptake In Primary Breast Tumorsmentioning
confidence: 99%